2016
DOI: 10.1039/c6ce01144f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and phase transitions of a layered perovskite-like CsScF4crystal

Abstract: This work is devoted to the complex research on temperature phase transitions in a CsScF 4 crystal. The crystal structure was solved and refined at different temperatures by using the Rietveld method. Structural phase transitions were investigated by using the following spectroscopic methods, some of them for the first time: Brillouin spectroscopy, Raman spectroscopy, IR absorption spectroscopy and NMR. The symmetry analysis of the Brillouin zone center of all phases is presented. The vibrational spectra of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The dependencies F ( r ij ) are the same for all atom pairs: F ( r ij ) = λexp­(− r ij /ρ), where λ and ρ are the parameters characterizing selected pair interaction. To find the parameters of the model, the special optimization program was written and tested for several representative compounds. ,,, The crystal lattice stability conditions were taken into account. The parameters obtained for AgEu­(SO 4 ) 2 are shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…The dependencies F ( r ij ) are the same for all atom pairs: F ( r ij ) = λexp­(− r ij /ρ), where λ and ρ are the parameters characterizing selected pair interaction. To find the parameters of the model, the special optimization program was written and tested for several representative compounds. ,,, The crystal lattice stability conditions were taken into account. The parameters obtained for AgEu­(SO 4 ) 2 are shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies on almost all reported lithium, potassium, and sodium fluoroscandates have been performed. Recently, the structures of two members of the CsF-ScF 3 system, CsScF 4 and CsSc 3 F 10 , have been reported. , However, rubidium-containing fluoride compounds have been overlooked. Only the structure of the RT RbSc 3 F 10 polymorph has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that the main reasons for this lack of investigations are related to the high cost of ScF3 and the high corrosiveness and hygroscopicity of Rb and Cs fluorides. In the CsF-ScF3 system, only the structure of CsScF4 has been reported [7].…”
Section: Introductionmentioning
confidence: 99%